Conservative surgical approach for the treatment of odontogenic keratocyst - Letycia Maria Lopes de Oliveira; Daniela Cristina Braga de Lima; Nayara Teixeira de Araújo; Letícia Resente Davi; Luiz Fernando Barbosa de Paulo (Editorial Ciencias Médicas, 2018)
Introduction: The odontogenic keratocyst was recently reclassified in 2017 by the World Health Organization as a cystic lesion of epithelial development derived from the enamel organ or the dental lamina. It shows common characteristics to cysts such as slow and continuous growth; however, it arouses attention for its high aggressiveness and recurrence rate. Objective: To show marsupialization followed by enucleation as a definitive treatment of odontogenic keratocysts. Clinical case: A 63-year-oldwoman with odontogenic keratocyst on the left side of the mandible, treated by the marsupialization technique followed by enucleation. Conclusions: Although there are various treatment options, the dental surgeon may prefer the conservative method in the approach of the odontogenic keratocyst, because it presents the lowest rate of morbidity and relapse within the standards presented in the literature.